Effect of pig serum storage conditions on detection of anti-ASFV antibodies by ELISA - A. R. Shotin; I. Yu. Zhukov; A. S. Pershin; Ali Mazloum; I. V. Shevchenko; A. S. Igolkin; O. A. Manuylova; K. N. Gruzdev (Ветеринария сегодня)
One of the measures used to control and prevent African swine fever spread in the Russian Federation involves testing pig and boar sera using inter alia serological tools based on enzyme-linked immunosorbent assay (ELISA) for anti-viral antibody detection. However, there is no unified regulatory document specifying storage conditions for sera used in the ELISA for anti-ASFV antibody detection. There are also lack of published data on the maximum admissible shelf life of the pig sera, and the effect of storage conditions on the serological status of the pig sera as for ASF is understudied. The paper demonstrates results of the experiment aimed at the determination of the effect of storage temperatures and shelf life on the serological status of ASFV seropositive and seronegative pig sera when tested by INgezim PPA Compac (Ingenasa, Spain) ELISA as well as on the possibility of false results. During the experiment and analysis of its results, the new data were obtained, and they indicated from none to non-significant effect of the simulated storage conditions on the serological status of sera used for ASFV detection, while hemolyzed sera demonstrated more significant changes proportional to hemolysis degree and storage duration. Although the results of detection of antibodies against the agents of some diseases cannot be used in case of other pathogens, this study has a substantial applied significance as it allows to specify the dependence of the valid results of ASF serodiagnosis on the storage conditions of the samples.